ECONOMY OF FRUIT TREES PRODUCTION - Milić, Dušan; Dimitrijević, Bojan; Kukić, Đuro (Economics of Agriculture, 2006)
Intensive and high-quality fruit production can not be realised without qualitative and well organized fruit trees production. Due to that fact, fruit trees production can be considered as the basis of fruit production. Within analised period (2002 - 2004) in fruit trees production unsatisfactory financial result had been realised (43.922 dinars). However, in spite of constant growth of production costs and insignificant growth of production value, in average, there had been realised economical production (economy coefficient 1,05). In average, it means that with 1 dinar of production costs there had been realised 1,05 dinars of production value.